HCV Infection and Cryoglobulinemia - Dammacco, Franco; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2012)
In 1947, Lerner and Watson showed that the cold-precipitable proteins in serum were gammaglobulins. These (3z(Bcryoglobulins(3y (Bwere responsible for the corresponding clinical condition (3z(Bcryoglobulinemia.(3y (BMeltzer and Franklin, in 1966, provided an accurate description of the typical clinical symptoms associated with cryoglobulinemia. Subsequent progress in this field was rather slow until the end of the 1980s, when cryoglobulinemia was definitively shown to be an extrahepatic manifestation of hepatitis C virus infection. The book is unique in its detailed presentation and fundamental approach. Highly qualified authors have contributed critical articles reviewing significant developments in our understanding of and therapeutic approach to HCV infection and cryoglobulinemia. The text is accompanied by striking color images and illustrations and highly informative tables. This comprehensive review of a systemic disease with a complex etiology is a valuable source of up-to-date, expert information not only for basic scientists and specialists in several disciplines but also for general practitioners as well as graduate and post-graduate students in clinical and medical research.s
Hepatitis C virus infection and the role of the immune system -- Cryoglobulinemia: immunochemical characterization, serological abnormalities and histopathological changes -- Structural and genetic features, cytokines and chemokines in cryoglobulinemia -- Cellular compartments of HCV infection (and replication) - Mechanism(s) of cryoprecipitation -- Clinical manifestations of cryoglobulinemia -- HCV infection, cryoglobulinemia and non-Hodgkin$1 (Bs lymphomas -- Therapy of cryoglobulinemia.s
Keywords: Medicine; Internal medicine; Clinical medicine; Emerging infectious diseases; Oncology; Rheumatology; Medicine & Public Health; Hepatology; Internal Medicine; Infectious Diseases; Rheumatology; Oncology